Disseminated Mycobacterium Haemophilum Infection Masquerading as Erythema Nodosum and Avascular Necrosis in an Immunocompromised Host. Issue 5 (September 2018) - Sainato, Rebecca J.; Smith, Benjamin R.; Parekh, Dina S.; Flores, Michelle S.; Logemann, Nicholas F.; Chung, Ellen M.; Eberly, Matthew D.; Stagliano, David R.; Malloy, Allison M.W.
Abstract : Abstract: Mycobacterium haemophilum is likely an underrecognized cause of infection among patients with deficits in their cell-mediated immunity. Despite its name, which translates to "blood loving, " it remains unclear whether hyperferritinemic patients are also at higher risk of this infection. We present a 24-year-old woman with disseminated M. haemophilum infection who has hyperferritinemia and T-cell acute lymphoblastic leukemia in remission and was initially misdiagnosed as having erythema nodosum and avascular necrosis. This report highlights the clinical and histological similarities of M. haemophilum and erythema nodosum, discusses some diagnostic peculiarities, and also reviews similar cases within the literature. Abstract : Mycobacterium haemophilum is likely an underrecognized cause of infection among patients with deficits in their cell-mediated immunity. Despite its name, which translates to "blood-loving, " it remains unclear whether hyperferritinemic patients are also at higher risk of this infection. This report highlights the clinical and histologic similarities of M. haemophilum and erythema nodosum, discusses some diagnostic peculiarities, and reviews similar cases within the literature.